LIFESTYLE HABITS, KNOWLEDGE AND PREVENTION OF UTERINE CERVIX CANCER (Fiep Bulletin - online, 2016)
Objective: indentify the lifestyle habits, knowledge and prevention of Uterine Cervix Cancer (UCC) among users of the primary health care unit of Caico-RN. Method: descriptive study, with a quantitative approach developed in the UBS Silvino Dantas, localized in the municipality of Caico/RN. The project was approved by the Research Ethics committee of the Integral College of Patos-PB CAAE n 3114021480005881. The population was constituted of 80 women registered in the unit and who accepted to participate in the research. An instrument produced by the researcher, was used for the collection of data , and was applied in the health unit abovementioned , in distinct days of the month of August 2014. The analysis of the data was carried out by simple statistics through graphs and tables and analyzed according to the pertinent literature. Results:  participated in the study young women, most of them single, with average educational levels, the majority of them (74%) had an active sexual life, 91,0% did not smoke, 42,0% drunk and 57,0% practiced physical exercise, 66,0% knew about aspects of UCC, 66,0% had the preventive screening examination periodically, 74,0% never had sexually transmitted infections and 14,0% presented a family history of UCC. Conclusion:  The women have healthy lifestyle habits which favor the prevention of neoplasms, and know about and have the gynecological examination with frequency.
Keywords: Uterine Cervix Cancer. Preventive Examination. Lifestyle Habits.